A (in) dependência dos pequenos municípios paranaenses ao FPM para a efetividade de suas funções federativas e contribuição para o desenvolvimento local - Oliveira, Débora Tazinasso de (2018)
After the promulgation of the 1988 Constitution, there has been a considerable expansion of the municipalities in Brazil, which led to the emergence of a large number of small municipalities. The point to be observed, however, in the assumption, is that the lower the municipality, the greater the difficulty in maintaining the minimum structure for its sustainability and, therefore, does not necessarily constitute a positive element for local development, self-difficulty to develop and fulfill its federal functions. That can make them dependent on external (intergovernmental) transfers. In this context, the present study has the objective of studying the financial capacity of Paraná municipalities with less than 10,000 inhabitants, for the execution of federative functions and impacts on local development. To reach the objective, the research classifies the approach as quantitative research. As for nature, it is applied research. As for the objectives, it is descriptive and explanatory research. Regarding the study design, it is a bibliographic and documentary research. Data collection was performed through documental research and quantitative data analysis. The assumptions regarding the purpose of the study are summarized in two, the first is that the small municipalities of Paraná, because they do not have the financial capacity to meet their federative functions, are dependent on intergovernmental external transfers to provide basic services to the population. The second assumption is that there is a positive correlation between the financial capacity of the municipalities and the result of the Ipardes Municipal Development Index (IMDI): the higher the financial capacity, the higher the IMDI result. Resulting, therefore, more municipal development. As a result, the small municipalities of Paraná presented a high degree of dependence on external transfers (Municipal Participation Fund), low Financial Capacity (FC) and Collection Capacity (CC). They are effective in performing their federal functions (health and education) based on IMDI results, but dependent on other larger municipalities for the provision of more complex public services. Finally, the linear correlation / regression analysis allows inferring that there is a positive correlation between the variables, however, the result was low and not significant for the study, representing that the Financial Capacity influences, but not significantly, in the Local Development of the small municipalities.